Ocular symptoms in COVID-19 patients with a history of hospitalization in the first pandemic wave in Styria, Austria - Andreas Guttmann; Astrid Heidinger; Nora Woltsche; Marianne Brodmann; Katharina Kurzmann-Gütl; Viktoria Nemecz; Matthias Kaindl; Herbert Wurzer; Gerold Schwantzer; Jutta Horwath-Winter (Frontiers in Ophthalmology)
PurposeOur study aimed to investigate the prevalence and timing of ocular surface manifestations in hospitalized COVID-19 patients, providing insights into the occurrence of eye involvement before, during, or after the illness. This study contributes to understanding the extent of ocular involvement in COVID-19, which has been suggested to occur due to potential viral entry through the eyes.Methods451 confirmed COVID-19 patients had a history of hospitalization in Styria, Austria. The study included 176 patients aged 18-95 years who tested positive for SARS-CoV-2 in nasopharyngeal swabs by RT-PCR and received treatment at two hospitals. Telephone interviews were conducted after recovery, focusing on ocular symptoms and medical history (openMEDOCS).ResultsSeventeen percent (n=30) reported new-onset ocular symptoms in the context of COVID-19. Patients with ocular symptoms were younger (p<0.001). Sore throat (p=0.013) and high fever (p=0.038) were significantly more prevalent in patients with new-onset ocular symptoms. Persistent ocular symptoms beyond the duration of hospitalization affected more than half (56.7%) of the participants with new-onset ocular symptoms. However, there were no differences in blood parameters, lung imaging, or comorbidities between groups with and without ocular symptoms.ConclusionsIn hospitalized COVID-19 patients, ocular symptoms occur with a significant prevalence of 17%. Younger age (p<0.001) and the presence of sore throat (p=0.013) are associated with an increased risk of developing new-onset ocular symptoms in the context of COVID-19.